Family Business Resilience: A Systematic Literature Review on Crisis Management and Long-Term Success - Arifin Djakasaputra; Juliana Juliana; Amelda Pramezwary; Diena M. Lemy (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
Family businesses play a vital role in the global economy, yet their unique structure and dynamics often expose them to significant vulnerabilities, particularly during crises. This systematic literature review aims to explore the resilience of family businesses, focusing on how they manage crises and maintain long-term success. By analyzing a wide range of studies published between 2015-2024, this review identifies critical factors influencing family business resilience, including leadership succession, financial management, governance structures, and family dynamics. Furthermore, the study sheds light on the role of family values and culture in fostering resilience, offering insights into how family-owned enterprises can achieve sustainable growth amidst uncertainty. The findings contribute to the existing body of knowledge by providing a comprehensive overview of resilience-building strategies and their impact on the long-term survival of family businesses, serving as a valuable resource for researchers and practitioners in the field of family business management